Motilitas dan Viabilitas Spermatozoa Itik Lokal (Anas platyrhyncos) Setelah Penyimpanan dalam Medium Berbeda Dikombinasi Krioprotektan Kuning Telur Berbagai Konsentrasi - Yusni Atifah; Dadang Mulyadi Saleh; Hendro Pramono; Yulia Sistina (Fakultas Biologi | Universitas Jenderal Soedirman, 2013)
The purpose of this study is to asses motility and viability of domestic duck (Anas platyrhyncos) spermatozoa after 6 day storing in preservation medium of different egg yolk cryoprotectant concentration in three different medium Tris, PBS or Ringer lactate. In this experiment, we applied 3 combination of factors as treatments : extender (Tris, PBS or Ringer lactate), egg yolk (EY) concentration (0, 5, 10, 15 or 25%) and storage time (0,1,2,3,4,5,6 days). Spermatozoa was obtained by massage technique, ejaculate then were swup up in the extender, the swup-up sperm then were incubated in preservation medium as each treatments subjected to motility and viability assesment before and after storage at refrigerator temperature (50C). The results showed that sperm motility and viability were highly significantly different (P<0.01) among 107 treatments. Extender factor as well as storage duration time were highly significantly different (P<0.01) affected the motility and viability of the treated sperm. EY concentration was significantly (P<0.05) affected viability, however there were no factor (P>0.05) affected motility of the sperm. The best treatment resulted in promising quality having the highest motility of 46,67 ± 32,15 5 motile was from the treatment of 10% EY in PBS stored for 4 days. The best viability result was from the tretament of 25% EY in PBS after 4 days storage resulted in 50,00 ± 36,05 % of viabie sperm. In conclusion this protocol could be applied for artificial insemination trial.